Types of employment contracts and elasticity of employment in the European Union new member states in 2000–2014 - Kwiatkowski, Eugeniusz; Włodarczyk, Przemysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The article is focused on the problem of elasticity of employment in the economies of the European Union new member states in 2000–2014. Special attention is given to the role of types of employment contracts and their influence on the elasticity of employment. Theoretical arguments and empirical observations enable us to formulate hypothesis about a U‑shaped relationship between the share of fixed‑term employment in total employment and elasticity of employment in a given economy. We should also expect increases of price and working time elasticity in response to increases in the share of fixed‑term employment. Results of panel model estimations performed using the data for 13 new European Union member states in 2000–2014 confirm the hypothesis about an impact of share of fixed‑term employment in total employment on the elasticity of employment. In particular, an increase in the number of fixed‑term contracts results in the fall of elasticity of employment with respect to GDP and increase in the elasticity of employment with respect to real wages and working time. There is however no confirmation of the hypothesis concerning a U‑shaped relationship between elasticity of employment with respect to GDP and the share of fixed‑term emplyment.